Centralizers of sl(2,1) and sl(1,2) in the Generalized Witt Lie Superalgebra over Fields of Prime Characteristics - LIU Jiaqi; QIAN Qiguo; ZHENG Keli (Journal of Harbin University of Science and Technology)
Centralizers of the special linear Lie superalgebra sl( 2， 1) and sl( 1， 2) on the generalized Witt Lie superalgebra are studied． By solving linear equations and comparing centralizers of the even and odd parts of gl( 2， 1) and gl( 2， 1) ，centralizers of sl( 2， 1) and sl( 1， 2) in the generalized Witt Lie superalgebra over fields of prime characteristic are determined．